Sensitivitas dan Kelayakan Indeks Biotik Menggunakan Makroavertebrata untuk Menentukan Status Kesehatan Sungai - Luk luk Il Maknuun; Majariana Krisanti; Yusli Wardiatno (Jurnal Ilmu Pertanian Indonesia, 2021)
Water-quality monitoring using macroinvertebrates has been developed by several countries to determine their water qualities. Meanwhile in Indonesia, water quality monitoring has not been developed to adapt to Indonesia’s natural conditions. Some researchers use the existing biotic indices such as FBI, LQI, SIGNAL, and others. Therefore, this study aims to determine the status of water quality using several biotic indices and to compare the sensitivity and feasibility of indices on monitoring activities using simple matrix and Pearson correlation test. The interpretation results of FBI, LQI, and Singscore to determine water quality on each station in Brantas, Opak, Progo, and Cileungsi Rivers were different. The Pearson’s correlations test showed that the sensitivities are different between rivers. Those results are affected by the river conditions and also the activities around the rivers which release the pollution into the river. The FBI index showed the greatest score number of sensitivities among the other indexes. Keywords: macroinvertebrate, monitoring, river, sensitivity